Heavy metal contamination in unrecorded rakia from Kosovo and its public health implications - Teuta Muhollari; Sándor Szűcs; Martin McKee; Róza Ádány; Zsófi Sajtos; Edina Baranyai; László Pál (Scientific Reports)
Abstract Excessive alcohol consumption poses a challenge to public health across Europe, but especially in the Balkan region, where alcohol from unrecorded sources, particularly home-distilled rakia, is widely consumed. Our previous research identified elevated lead and copper levels in rakia from these sources collected in Albania. However, due to its disputed political status and absence from many international health surveys, data on the composition of home-made rakia from Kosovo remains scarce. To address this knowledge gap, we report an analysis of 30 rakia samples from unrecorded sources collected in Kosovo, measuring 24 elements, including toxic metals, using inductively coupled plasma optical emission spectrometry. The ethanol concentration of the samples was determined by gas chromatography/mass spectrometry. In addition, we have applied the target hazard quotient and the margin of exposure (MOE) methods to assess the associated health risks. We find that the threshold limits of copper, iron, nickel, and lead have been exceeded in 96.7%, 3.3%, 3.3% and 26.7% of rakia samples, respectively. The health risk assessment showed that the MOE value of lead for both average and heavy drinkers was less than 100 when consuming unrecorded rakia, indicating potential for adverse health effects. Along with previous research, these findings highlight the need for targeted public health research in the Balkan region to better understand the impact of unrecorded alcohol on disease burden and mortality and how to develop policies that strengthen enforcement of trading standards.